Association of Iron Deficiency Anaemia and Febrile Seizures in Children - Tariq Saeed, Muhammad Zahoor Ul Haq, Asma Kanwal, Rubina Zulfiqar, Tariq Mahmood Raja (Journal of Rawalpindi Medical College, 2013)
deficiency anaemia with febrile seizures. Methods: In this descriptive study 100 patients were selected. Out of these 100 subjects, 50 were control who had fever but did not have seizures and 50 were cases presenting with febrile seizures. Serum ferritin level was checked in both groups and an intergroup comparison was undertaken. Results: Mean age of patients without febrile seizures (control) was 13 months while mean age of patients with febrile seizures (cases) was 16.4 months. In patients without febrile seizures, mean serum ferritin level was 7.9 μg/L whereas in patients with febrile seizures; the mean serum ferritin level was 6.9 μg/L. Serum ferritin level was significantly lower in children with febrile seizures in comparison with the children in control group(p value of 0.028) Conclusion: There is positive association of iron deficiency with febrile seizure. In children with febrile fits ,iron deficiency should be excluded